Bioethics and scientific information - Sinaccio, Graziella; Robert, Elisabetta; Spagnolo, Antonio G. (Medicina e Morale, 1996)
Scientific information represents today a precious blessing to enrich with culture, science, education, seriousness and ethics. The Authors consider three different subjects to whom IS is addressed: scientists, public, and patient. Ars communicandi can't ignore this distinction evaluating the most convenient language for every receiver in order that the message is comprehended. Who intends to spread science has the great responsibility to do it with truth, correctly, avoiding unnecessary alarms and false hopes, covering the way suggested by the principles of Bioethics.